Analysis of the Implementation of the Talking Stick Cooperative Learning Model in Enhancing Students’ Learning Activeness in Islamic Religious Education at MI Al-Awwal Palembang - Melya, Trianita; Nurlaeli; Agra Dwi Saputra; Aquami; Ines Tasya Jadidah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Student activeness in the learning process is one of the key indicators that supports learning success. At MI Al-Awwal Palembang, teachers strive to create an interactive learning atmosphere through the implementation of various learning models, one of which is the cooperative learning model of the talking stick type. This study aims to describe the implementation of the talking stick cooperative learning model, the students’ learning activeness, as well as the supporting and inhibiting factors during the learning process. This research employed a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The research subjects were 26 students of class V.A and a teacher of Islamic Religious Education (PAI). The findings indicate that the implementation of the talking stick cooperative learning model successfully created a participatory and engaging learning environment, in which students became more active in expressing their opinions, answering questions, and collaborating in groups. The supporting factors for the success of this model include the teacher’s communication skills, the availability of facilities such as the stick and speaker, and the students’ enthusiasm. However, challenges were found in classroom management, such as a less conducive atmosphere during the stick relay activity, which requires further attention and improvement. Overall, the implementation of the talking stick cooperative learning model has had a positive impact on increasing students’ learning activeness in Islamic Religious Education.